Lineage is an Epigenetic Modifier of QTL Influencing Behavioral Coping with Stress - Ahmadiyeh, Nasim (2005)
A genome-wide scan was carried out on a segregating F2 population of rats derived from reciprocal intercrosses between two inbred strains of rats, Fisher 344 (F344) and Wistar Kyoto (WKY) that differ significantly in their behavioral coping responses to stress measured by the defensive burying (DB) test. The DB test measures differences in coping strategies by assaying an animal’s behavioral response to an immediate threat. We have previously identified three X-linked loci contributing to the phenotypic variance in behavioral coping. Here we report on six significant autosomal quantitative trait loci (QTL) related to different behaviors in the DB test:one for the number of shocks received, three for number of prod approaches, one for latency to bury, and one pleiotropic locus affecting both approach and latency. These QTL contributing to different aspects of coping behaviors show that the effect of genotype on phenotype is highly dependent on lineage. The WKY lineage was particularly influential, with five out of the six QTL affecting coping behavior only in rats of the WKY lineage, and one locus affecting only those in the F344 lineage. Thus, epigenetic factors, primarily of WKY origin, may significantly modulate the genetic contribution to variance in behavioral responses to stress in the DB test.